Barriers to implementing a policy not to attempt resuscitation in acute medical admissions: prospective, cross sectional study of a successive cohort. Issue 7539 (10th February 2006) - Fidler, H; Thompson, C; Freeman, A; Hogan, D; Walker, G; Weinman, y
Abstract: Objective To establish whether acutely unwell patients admitted to hospital wish to participate in discussions about resuscitation. Design Prospective, cross sectional study of a successive cohort of patients. Setting Admission through the emergency department. Participants 374 adult patients. Main outcome measure Whether acutely unwell patients wished to participate in discussions about resuscitation. Results Of the total sample, 74 patients consented to take part in the study and provide full data. Of the remaining patients, 189 could not be approached for practical reasons and 111 did not wish to participate. Of the 74 patients who read the leaflet, 65 (88%) reported having little or no prior knowledge, 70 (96%) understood it, 56 (77.8%) preferred for resuscitation decisions to be discussed with them, and 55 (77.5%) did not mind discussing resuscitation within 24 hours of admission and overall showed a decline in their anxiety score. Conclusion Many patients admitted through the emergency department for medical reasons cannot participate in their decision not to attempt resuscitation within 24 hours of admission. Patients who were willing to participate rated the information leaflet that was provided positively.